Environment-friendly composite highlight powder coating and preparation method thereof

Through the combination of silicon-carbon modified polyester resin and filler, the problem of insufficient impact resistance and gloss of polyester resin powder coating is solved, and environmentally friendly composite high-gloss powder coating is prepared, achieving high leveling and high temperature stability. Application in multiple fields.

CN119192961AActive Publication Date: 2024-12-27ZHEJIANG LVHUAN NEW MATERIAL TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411415107.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2024-12-27
Estimated Expiration
2044-10-11
Patent Text Reader

Abstract

The invention discloses an environment-friendly composite highlight powder coating and a preparation method thereof, and relates to the technical field of coatings, the environment-friendly composite highlight powder coating is prepared from the following components: silicon carbon modified polyester resin, a curing agent, diatomite, an auxiliary agent, a composite filler, an antioxidant, tributyl citrate, calcium stearate, benzoin and a leveling agent; the powder coating prepared by the invention is a novel 100% solid powder coating which does not contain a solvent. The powder coating disclosed by the invention has the characteristics of no solvent, environmental protection, no pollution, recoverability, energy and resource saving, high mechanical strength of a coating film and the like, and is wide in application field and suitable for being used in multiple fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, in particular to an environmentally friendly composite high-gloss powder coating and a preparation method thereof. Background Art

[0002] Powder coating is a solid powdered synthetic resin coating composed of solid resin, filler and additives. Unlike ordinary solvent-based coatings and water-based coatings, its dispersion medium is air instead of solvent and water. It has the characteristics of no solvent pollution, 100% film formation and low energy consumption. Powder coatings are divided into two categories: thermoplastic and thermosetting. Thermoplastic powder coatings have poor coating appearance (gloss and leveling) and poor adhesion to metal, which limits its application in many fields. Thermosetting powder coatings use thermosetting synthetic resin as the film-forming material. During the drying process, the resin first melts and then solidifies into a smooth and hard coating film after chemical cross-linking. The coating film appearance, various mechanical properties and corrosion resistance formed by this type of coating can meet the requirements of many fields.

[0003] As an important type of powder coating, polyester powder coating has good weather resistance and climate stability, good adhesion ability, and good bonding strength with a variety of substrates.

[0004] However, powder coatings with polyester resin as the main film-forming material have relatively poor impact resistance and significantly lower gloss of the coating due to the insufficient bond energy of C-O and C-C bonds.

[0005] Based on this, an environmentally friendly composite high-gloss powder coating and a preparation method thereof are provided to solve the existing technical problems. Summary of the invention

[0006] The purpose of the present invention is to provide an environmentally friendly composite high-gloss powder coating and a preparation method thereof, so as to solve the deficiencies in the prior art.

[0007] The technical solution adopted by the present invention is as follows:

[0008] An environmentally friendly composite high-gloss powder coating comprises the following ingredients by weight: 90-98 parts of silicon-carbon modified polyester resin, 5-9 parts of curing agent, 5-8 parts of diatomaceous earth, 0.5-0.8 parts of auxiliary agent, 18-23 parts of composite filler, 0.5-0.8 parts of antioxidant, 1-2 parts of tributyl citrate, 1.5-3 parts of calcium stearate, 0.5-1 parts of benzoin and 1-2 parts of leveling agent.

[0009] As a further technical solution: the preparation method of the auxiliary agent is:

[0010] (1) First, methyl methacrylate is added into a reaction kettle, and then an organic solvent is added into the reaction kettle, the temperature is adjusted to 65° C., the mixture is kept warm, and the mixture is stirred and mixed at a speed of 150 r / min for 15 min to obtain a base liquid;

[0011] (2) adding an initiator to the same organic solvent as in step (1), stirring and mixing at room temperature at a speed of 150 r / min to obtain an initiator solution;

[0012] (3) The initiator solution prepared in step (2) is added dropwise to the reactor in step (1), and then the mixture is stirred and kept warm at 70° C. for 1.5 hours. A portion of the organic solvent is first removed by atmospheric distillation, and then the remaining organic solvent is removed by reduced pressure distillation. Finally, the mixture is crushed and then sieved through a 350-mesh sieve to obtain an auxiliary agent.

[0013] As a further technical solution: the organic solvent is xylene;

[0014] The mixing mass ratio of xylene to methyl methacrylate is 35:5-8;

[0015] The initiator is dibenzoyl peroxide;

[0016] The mass fraction of the initiator solution is 3.25%;

[0017] The mixing mass ratio of the initiator solution to the base liquid is 1:6-8.

[0018] As a further technical solution: the preparation method of the silicon-carbon modified polyester resin is:

[0019] Octamethylcyclotetrasiloxane and tetramethyltetravinylcyclotetrasiloxane are added to a reaction kettle in a molar ratio of 3:1-2, and then heated to 50°C, stirred for 30 minutes, and then graphene is added, and the mixture is evacuated to 0.5 Pa, stirred for 2 hours, and then maleic anhydride, a catalyst, and a coupling agent are added, and the temperature is adjusted to 80°C, stirred for 4 hours, and then cooled, discharged, and dried to obtain a modifier;

[0020] The modifier and polyester resin obtained above are added to a twin-screw extruder for melt extrusion and granulation to obtain a silicon-carbon modified polyester resin.

[0021] As a further technical solution: the mixing mass ratio of the octamethylcyclotetrasiloxane, graphene, maleic anhydride, catalyst and coupling agent is 10:1-3:2:0.5:1.

[0022] As a further technical solution: the catalyst is: potassium persulfate;

[0023] The coupling agent is a titanate coupling agent.

[0024] As a further technical solution: the mass ratio of the modifier to the polyester resin is 3-5:40-45.

[0025] As a further technical solution: the curing agent is curing agent T105;

[0026] The leveling agent is polyacrylate;

[0027] The antioxidant is 1010.

[0028] As a further technical solution: the composite filler is titanium dioxide, calcium titanate, and zeolite powder;

[0029] The mixing mass ratio of the titanium dioxide, calcium titanate and zeolite powder is 3:15:1.

[0030] A method for preparing an environmentally friendly composite high-gloss powder coating comprises the following steps:

[0031] S1. First, add silicon-carbon modified polyester resin, curing agent, diatomaceous earth, additives, composite fillers, antioxidants, tributyl citrate, calcium stearate, benzoin, and leveling agent into a mixer, stir and mix for 15 minutes, heat to 120°C under negative pressure, and continue stirring for 20 minutes until the mixture is mixed;

[0032] The mixing speed is 550r / min;

[0033] S2. adding the mixture to a twin-screw extruder and subjecting it to melt extrusion;

[0034] S3. After the melt is extruded through a twin-screw extruder, it is transported to a tablet press for tableting to obtain a sheet, and then the sheet is crushed, sieved, and packaged to obtain an environmentally friendly composite high-gloss powder coating;

[0035] Among them, the average particle size of the environmentally friendly composite high-gloss powder coating is 40μm.

[0036] Beneficial effects:

[0037] The powder coating prepared by the present invention is a new type of solvent-free, 100% solid powder coating. The powder coating of the present invention has the characteristics of being solvent-free, environmentally friendly, pollution-free, recyclable, energy and resource-saving, and having high mechanical strength of the coating film. It has a wide range of applications and is suitable for use in multiple fields.

[0038] The present invention can effectively reduce the melt viscosity of the overall resin by modifying the polyester resin, thereby greatly improving the impact resistance and leveling performance of the coating formed by the powder coating, and also greatly improving the temperature resistance of the coating. The coating formed by the powder coating prepared by the present invention can be used for a long time at 350°C, which greatly broadens the use of the powder coating in high temperature fields.

[0039] Due to the special modification of polyester resin in the present invention, mainly silicon and carbon are introduced, which can effectively avoid the problem of easy agglomeration of powder coating in high temperature environment, thereby effectively ensuring the normal spraying of powder coating and improving the convenience of spraying. In addition, the powder coating prepared by the present invention has a good leveling appearance after curing, which can effectively form a high leveling decorative effect and greatly improve the quality of the coating.

[0040] The introduction of conventional leveling agents improves the leveling performance of the coating to a certain extent, but it is still difficult to achieve a high leveling degree of the prepared coating. Therefore, the present invention introduces a variety of active groups by modifying the polyester resin, and the use of a leveling agent can further improve the leveling performance of the coating. DETAILED DESCRIPTION

[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] Example 1

[0043] The invention discloses an environmentally friendly composite high-gloss powder coating, which comprises the following components by weight: 90 parts of silicon-carbon modified polyester resin, 5 parts of curing agent, 5 parts of diatomaceous earth, 0.5 parts of auxiliary agent, 18 parts of composite filler, 0.5 parts of antioxidant, 1 part of tributyl citrate, 1.5 parts of calcium stearate, 0.5 parts of benzoin and 1 part of leveling agent.

[0044] The preparation method of the auxiliary agent is:

[0045] (1) First, methyl methacrylate is added into a reaction kettle, and then an organic solvent is added into the reaction kettle, the temperature is adjusted to 65° C., the mixture is kept warm, and the mixture is stirred and mixed at a speed of 150 r / min for 15 min to obtain a base liquid;

[0046] (2) adding an initiator to the same organic solvent as in step (1), stirring and mixing at room temperature at a speed of 150 r / min to obtain an initiator solution;

[0047] (3) The initiator solution prepared in step (2) is added dropwise to the reactor in step (1), and then the mixture is stirred and kept warm at 70° C. for 1.5 hours. A portion of the organic solvent is first removed by atmospheric distillation, and then the remaining organic solvent is removed by reduced pressure distillation. Finally, the mixture is crushed and then sieved through a 350-mesh sieve to obtain an auxiliary agent.

[0048] The organic solvent is xylene;

[0049] The mixing mass ratio of xylene to methyl methacrylate is 35:5;

[0050] The initiator is dibenzoyl peroxide;

[0051] The mass fraction of the initiator solution is 3.25%;

[0052] The mixing mass ratio of the initiator solution and the base liquid is 1:6.

[0053] The preparation method of silicon-carbon modified polyester resin is as follows:

[0054] Octamethylcyclotetrasiloxane and tetramethyltetravinylcyclotetrasiloxane were added to a reaction kettle in a molar ratio of 3:1, and then heated to 50°C, stirred for 30 minutes, and then graphene was added, and the mixture was evacuated to 0.5 Pa, stirred for 2 hours, and then maleic anhydride, a catalyst, and a coupling agent were added, and the temperature was adjusted to 80°C, stirred for 4 hours, and then cooled, discharged, and dried to obtain a modifier;

[0055] The modifier and polyester resin obtained above are added to a twin-screw extruder for melt extrusion and granulation to obtain a silicon-carbon modified polyester resin.

[0056] The mixing mass ratio of octamethylcyclotetrasiloxane, graphene, maleic anhydride, catalyst and coupling agent is 10:1:2:0.5:1.

[0057] The catalyst is: potassium persulfate;

[0058] The coupling agent is a titanate coupling agent.

[0059] The mixing mass ratio of the modifier to the polyester resin is 3:40.

[0060] The curing agent is curing agent T105;

[0061] The leveling agent is polyacrylate;

[0062] The antioxidant is 1010.

[0063] The composite filler is titanium dioxide, calcium titanate, and zeolite powder;

[0064] The mixing mass ratio of the titanium dioxide, calcium titanate and zeolite powder is 3:15:1.

[0065] A method for preparing an environmentally friendly composite high-gloss powder coating comprises the following steps:

[0066] S1. First, add silicon-carbon modified polyester resin, curing agent, diatomaceous earth, additives, composite fillers, antioxidants, tributyl citrate, calcium stearate, benzoin, and leveling agent into a mixer, stir and mix for 15 minutes, heat to 120°C under negative pressure, and continue stirring for 20 minutes until the mixture is mixed;

[0067] The mixing speed is 550r / min;

[0068] S2. adding the mixture to a twin-screw extruder and subjecting it to melt extrusion;

[0069] S3. After the melt is extruded through a twin-screw extruder, it is transported to a tablet press for tableting to obtain a sheet, and then the sheet is crushed, sieved, and packaged to obtain an environmentally friendly composite high-gloss powder coating;

[0070] Among them, the average particle size of the environmentally friendly composite high-gloss powder coating is 40μm.

[0071] Example 2

[0072] The invention discloses an environmentally friendly composite high-gloss powder coating, which comprises the following components by weight: 92 parts of silicon-carbon modified polyester resin, 6 parts of curing agent, 7 parts of diatomaceous earth, 0.55 parts of auxiliary agent, 20 parts of composite filler, 0.6 parts of antioxidant, 1.5 parts of tributyl citrate, 1.8 parts of calcium stearate, 0.7 parts of benzoin and 1.2 parts of leveling agent.

[0073] The preparation method of the auxiliary agent is:

[0074] (1) First, methyl methacrylate is added into a reaction kettle, and then an organic solvent is added into the reaction kettle, the temperature is adjusted to 65° C., the mixture is kept warm, and the mixture is stirred and mixed at a speed of 150 r / min for 15 min to obtain a base liquid;

[0075] (2) adding an initiator to the same organic solvent as in step (1), stirring and mixing at room temperature at a speed of 150 r / min to obtain an initiator solution;

[0076] (3) The initiator solution prepared in step (2) is added dropwise to the reactor in step (1), and then the mixture is stirred and kept warm at 70° C. for 1.5 hours. A portion of the organic solvent is first removed by atmospheric distillation, and then the remaining organic solvent is removed by reduced pressure distillation. Finally, the mixture is crushed and then sieved through a 350-mesh sieve to obtain an auxiliary agent.

[0077] The organic solvent is xylene;

[0078] The mixing mass ratio of xylene to methyl methacrylate is 35:6;

[0079] The initiator is dibenzoyl peroxide;

[0080] The mass fraction of the initiator solution is 3.25%;

[0081] The mixing mass ratio of the initiator solution and the base liquid is 1:7.

[0082] The preparation method of silicon-carbon modified polyester resin is as follows:

[0083] Octamethylcyclotetrasiloxane and tetramethyltetravinylcyclotetrasiloxane were added to a reaction kettle at a molar ratio of 3:1.5, and then heated to 50°C, stirred for 30 minutes, and then graphene was added, and the mixture was evacuated to 0.5 Pa, stirred for 2 hours, and then maleic anhydride, a catalyst, and a coupling agent were added, and the temperature was adjusted to 80°C, stirred for 4 hours, and then cooled, discharged, and dried to obtain a modifier;

[0084] The modifier and polyester resin obtained above are added to a twin-screw extruder for melt extrusion and granulation to obtain a silicon-carbon modified polyester resin.

[0085] The mixing mass ratio of octamethylcyclotetrasiloxane, graphene, maleic anhydride, catalyst and coupling agent is 10:2:2:0.5:1.

[0086] The catalyst is: potassium persulfate;

[0087] The coupling agent is a titanate coupling agent.

[0088] The mixing mass ratio of the modifier to the polyester resin is 3.5:42.

[0089] The curing agent is curing agent T105;

[0090] The leveling agent is polyacrylate;

[0091] The antioxidant is 1010.

[0092] The composite filler is titanium dioxide, calcium titanate, and zeolite powder;

[0093] The mixing mass ratio of the titanium dioxide, calcium titanate and zeolite powder is 3:15:1.

[0094] A method for preparing an environmentally friendly composite high-gloss powder coating comprises the following steps:

[0095] S1. First, add silicon-carbon modified polyester resin, curing agent, diatomaceous earth, additives, composite fillers, antioxidants, tributyl citrate, calcium stearate, benzoin, and leveling agent into a mixer, stir and mix for 15 minutes, heat to 120°C under negative pressure, and continue stirring for 20 minutes until the mixture is mixed;

[0096] The mixing speed is 550r / min;

[0097] S2. adding the mixture to a twin-screw extruder and subjecting it to melt extrusion;

[0098] S3. After the melt is extruded through a twin-screw extruder, it is transported to a tablet press for tableting to obtain a sheet, and then the sheet is crushed, sieved, and packaged to obtain an environmentally friendly composite high-gloss powder coating;

[0099] Among them, the average particle size of the environmentally friendly composite high-gloss powder coating is 40μm.

[0100] Example 3

[0101] The invention discloses an environmentally friendly composite high-gloss powder coating, which comprises the following components by weight: 95 parts of silicon-carbon modified polyester resin, 7 parts of curing agent, 6 parts of diatomaceous earth, 0.6 parts of auxiliary agent, 21 parts of composite filler, 0.6 parts of antioxidant, 1.6 parts of tributyl citrate, 2 parts of calcium stearate, 0.8 parts of benzoin and 1.5 parts of leveling agent.

[0102] The preparation method of the auxiliary agent is:

[0103] (1) First, methyl methacrylate is added into a reaction kettle, and then an organic solvent is added into the reaction kettle, the temperature is adjusted to 65° C., the mixture is kept warm, and the mixture is stirred and mixed at a speed of 150 r / min for 15 min to obtain a base liquid;

[0104] (2) adding an initiator to the same organic solvent as in step (1), stirring and mixing at room temperature at a speed of 150 r / min to obtain an initiator solution;

[0105] (3) The initiator solution prepared in step (2) is added dropwise to the reactor in step (1), and then the mixture is stirred and kept warm at 70° C. for 1.5 hours. A portion of the organic solvent is first removed by atmospheric distillation, and then the remaining organic solvent is removed by reduced pressure distillation. Finally, the mixture is crushed and then sieved through a 350-mesh sieve to obtain an auxiliary agent.

[0106] The organic solvent is xylene;

[0107] The mixing mass ratio of xylene to methyl methacrylate is 35:6;

[0108] The initiator is dibenzoyl peroxide;

[0109] The mass fraction of the initiator solution is 3.25%;

[0110] The mixing mass ratio of the initiator solution and the base liquid is 1:7.

[0111] The preparation method of silicon-carbon modified polyester resin is as follows:

[0112] Octamethylcyclotetrasiloxane and tetramethyltetravinylcyclotetrasiloxane were added to a reaction kettle at a molar ratio of 3:1.5, and then heated to 50°C, stirred for 30 minutes, and then graphene was added, and the mixture was evacuated to 0.5 Pa, stirred for 2 hours, and then maleic anhydride, a catalyst, and a coupling agent were added, and the temperature was adjusted to 80°C, stirred for 4 hours, and then cooled, discharged, and dried to obtain a modifier;

[0113] The modifier and polyester resin obtained above are added to a twin-screw extruder for melt extrusion and granulation to obtain a silicon-carbon modified polyester resin.

[0114] The mixing mass ratio of octamethylcyclotetrasiloxane, graphene, maleic anhydride, catalyst and coupling agent is 10:2:2:0.5:1.

[0115] The catalyst is: potassium persulfate;

[0116] The coupling agent is a titanate coupling agent.

[0117] The mixing mass ratio of the modifier to the polyester resin is 4:43.

[0118] The curing agent is curing agent T105;

[0119] The leveling agent is polyacrylate;

[0120] The antioxidant is 1010.

[0121] The composite filler is titanium dioxide, calcium titanate, and zeolite powder;

[0122] The mixing mass ratio of the titanium dioxide, calcium titanate and zeolite powder is 3:15:1.

[0123] A method for preparing an environmentally friendly composite high-gloss powder coating comprises the following steps:

[0124] S1. First, add silicon-carbon modified polyester resin, curing agent, diatomaceous earth, additives, composite fillers, antioxidants, tributyl citrate, calcium stearate, benzoin, and leveling agent into a mixer, stir and mix for 15 minutes, heat to 120°C under negative pressure, and continue stirring for 20 minutes until the mixture is mixed;

[0125] The mixing speed is 550r / min;

[0126] S2. adding the mixture to a twin-screw extruder and subjecting it to melt extrusion;

[0127] S3. After the melt is extruded through a twin-screw extruder, it is transported to a tablet press for tableting to obtain a sheet, and then the sheet is crushed, sieved, and packaged to obtain an environmentally friendly composite high-gloss powder coating;

[0128] Among them, the average particle size of the environmentally friendly composite high-gloss powder coating is 40μm.

[0129] Example 4

[0130] The invention discloses an environmentally friendly composite high-gloss powder coating, which comprises the following components by weight: 96 parts of silicon-carbon modified polyester resin, 8 parts of curing agent, 7 parts of diatomaceous earth, 0.6 parts of auxiliary agent, 21 parts of composite filler, 0.7 parts of antioxidant, 1.5 parts of tributyl citrate, 2 parts of calcium stearate, 0.8 parts of benzoin and 1.4 parts of leveling agent.

[0131] The preparation method of the auxiliary agent is:

[0132] (1) First, methyl methacrylate is added into a reaction kettle, and then an organic solvent is added into the reaction kettle, the temperature is adjusted to 65° C., the mixture is kept warm, and the mixture is stirred and mixed at a speed of 150 r / min for 15 min to obtain a base liquid;

[0133] (2) adding an initiator to the same organic solvent as in step (1), stirring and mixing at room temperature at a speed of 150 r / min to obtain an initiator solution;

[0134] (3) The initiator solution prepared in step (2) is added dropwise to the reactor in step (1), and then the mixture is stirred and kept warm at 70° C. for 1.5 hours. A portion of the organic solvent is first removed by atmospheric distillation, and then the remaining organic solvent is removed by reduced pressure distillation. Finally, the mixture is crushed and then sieved through a 350-mesh sieve to obtain an auxiliary agent.

[0135] The organic solvent is xylene;

[0136] The mixing mass ratio of xylene to methyl methacrylate is 35:7;

[0137] The initiator is dibenzoyl peroxide;

[0138] The mass fraction of the initiator solution is 3.25%;

[0139] The mixing mass ratio of the initiator solution and the base liquid is 1:6.

[0140] The preparation method of silicon-carbon modified polyester resin is as follows:

[0141] Octamethylcyclotetrasiloxane and tetramethyltetravinylcyclotetrasiloxane were added to a reaction kettle in a molar ratio of 3:1, and then heated to 50°C, stirred for 30 minutes, and then graphene was added, and the mixture was evacuated to 0.5 Pa, stirred for 2 hours, and then maleic anhydride, a catalyst, and a coupling agent were added, and the temperature was adjusted to 80°C, stirred for 4 hours, and then cooled, discharged, and dried to obtain a modifier;

[0142] The modifier and polyester resin obtained above are added to a twin-screw extruder for melt extrusion and granulation to obtain a silicon-carbon modified polyester resin.

[0143] The mixing mass ratio of octamethylcyclotetrasiloxane, graphene, maleic anhydride, catalyst and coupling agent is 10:2:2:0.5:1.

[0144] The catalyst is: potassium persulfate;

[0145] The coupling agent is a titanate coupling agent.

[0146] The mixing mass ratio of the modifier to the polyester resin is 4:42.

[0147] The curing agent is curing agent T105;

[0148] The leveling agent is polyacrylate;

[0149] The antioxidant is 1010.

[0150] The composite filler is titanium dioxide, calcium titanate, and zeolite powder;

[0151] The mixing mass ratio of the titanium dioxide, calcium titanate and zeolite powder is 3:15:1.

[0152] A method for preparing an environmentally friendly composite high-gloss powder coating comprises the following steps:

[0153] S1. First, add silicon-carbon modified polyester resin, curing agent, diatomaceous earth, additives, composite fillers, antioxidants, tributyl citrate, calcium stearate, benzoin, and leveling agent into a mixer, stir and mix for 15 minutes, heat to 120°C under negative pressure, and continue stirring for 20 minutes until the mixture is mixed;

[0154] The mixing speed is 550r / min;

[0155] S2. adding the mixture to a twin-screw extruder and subjecting it to melt extrusion;

[0156] S3. After the melt is extruded through a twin-screw extruder, it is transported to a tablet press for tableting to obtain a sheet, and then the sheet is crushed, sieved, and packaged to obtain an environmentally friendly composite high-gloss powder coating;

[0157] Among them, the average particle size of the environmentally friendly composite high-gloss powder coating is 40μm.

[0158] Example 5

[0159] The invention discloses an environmentally friendly composite high-gloss powder coating, which comprises the following ingredients by weight: 98 parts of silicon-carbon modified polyester resin, 9 parts of curing agent, 8 parts of diatomaceous earth, 0.8 parts of auxiliary agent, 23 parts of composite filler, 0.8 parts of antioxidant, 2 parts of tributyl citrate, 3 parts of calcium stearate, 1 part of benzoin and 2 parts of leveling agent.

[0160] The preparation method of the auxiliary agent is:

[0161] (1) First, methyl methacrylate is added into a reaction kettle, and then an organic solvent is added into the reaction kettle, the temperature is adjusted to 65° C., the mixture is kept warm, and the mixture is stirred and mixed at a speed of 150 r / min for 15 min to obtain a base liquid;

[0162] (2) adding an initiator to the same organic solvent as in step (1), stirring and mixing at room temperature at a speed of 150 r / min to obtain an initiator solution;

[0163] (3) The initiator solution prepared in step (2) is added dropwise to the reactor in step (1), and then the mixture is stirred and kept warm at 70° C. for 1.5 hours. A portion of the organic solvent is first removed by atmospheric distillation, and then the remaining organic solvent is removed by reduced pressure distillation. Finally, the mixture is crushed and then sieved through a 350-mesh sieve to obtain an auxiliary agent.

[0164] The organic solvent is xylene;

[0165] The mixing mass ratio of xylene to methyl methacrylate is 35:8;

[0166] The initiator is dibenzoyl peroxide;

[0167] The mass fraction of the initiator solution is 3.25%;

[0168] The mixing mass ratio of the initiator solution and the base liquid is 1:8.

[0169] The preparation method of silicon-carbon modified polyester resin is as follows:

[0170] Octamethylcyclotetrasiloxane and tetramethyltetravinylcyclotetrasiloxane were added to a reaction kettle in a molar ratio of 3:2, and then heated to 50°C, stirred for 30 minutes, and then graphene was added, and the mixture was evacuated to 0.5 Pa, stirred for 2 hours, and then maleic anhydride, a catalyst, and a coupling agent were added, and the temperature was adjusted to 80°C, stirred for 4 hours, and then cooled, discharged, and dried to obtain a modifier;

[0171] The modifier and polyester resin obtained above are added to a twin-screw extruder for melt extrusion and granulation to obtain a silicon-carbon modified polyester resin.

[0172] The mixing mass ratio of octamethylcyclotetrasiloxane, graphene, maleic anhydride, catalyst and coupling agent is 10:3:2:0.5:1.

[0173] The catalyst is: potassium persulfate;

[0174] The coupling agent is a titanate coupling agent.

[0175] The mixing mass ratio of the modifier to the polyester resin is 5:45.

[0176] The curing agent is curing agent T105;

[0177] The leveling agent is polyacrylate;

[0178] The antioxidant is 1010.

[0179] The composite filler is titanium dioxide, calcium titanate, and zeolite powder;

[0180] The mixing mass ratio of the titanium dioxide, calcium titanate and zeolite powder is 3:15:1.

[0181] A method for preparing an environmentally friendly composite high-gloss powder coating comprises the following steps:

[0182] S1. First, add silicon-carbon modified polyester resin, curing agent, diatomaceous earth, additives, composite fillers, antioxidants, tributyl citrate, calcium stearate, benzoin, and leveling agent into a mixer, stir and mix for 15 minutes, heat to 120°C under negative pressure, and continue stirring for 20 minutes until the mixture is mixed;

[0183] The mixing speed is 550r / min;

[0184] S2. adding the mixture to a twin-screw extruder and subjecting it to melt extrusion;

[0185] S3. After the melt is extruded through a twin-screw extruder, it is transported to a tablet press for tableting to obtain a sheet, and then the sheet is crushed, sieved, and packaged to obtain an environmentally friendly composite high-gloss powder coating;

[0186] Among them, the average particle size of the environmentally friendly composite high-gloss powder coating is 40μm.

[0187] Comparative Example 1:

[0188] The difference from Example 1 is that no auxiliary agent is added, and the rest of the technical scheme remains unchanged.

[0189] Comparative Example 2:

[0190] The difference from Example 1 is that the silicon-carbon modified polyester resin is replaced by an unmodified polyester resin, and the rest of the technical solutions remain unchanged.

[0191] test:

[0192] Test Method

[0193] The coatings of the embodiment and the comparative example were sprayed onto the surface of the glass plate (10 samples in each group, and the final result was averaged), with the thickness difference not exceeding 0.05 mm. After curing under the same conditions, the glossiness of the coating was measured according to ISO2813:

[0194] Table 1

[0195] Glossiness Example 1 81 Example 2 84 Example 3 86 Example 4 79 Example 5 81 Comparative Example 1 51

[0196] It can be seen from Table 1 that the powder coating prepared by the present invention has a higher gloss after curing.

[0197] The gel time of powder coating is tested according to HG / T2006-2006, and the test temperature is 180℃:

[0198] Table 2

[0199] Gel time / s Example 1 568 Example 2 549 Example 3 553 Example 4 557 Example 5 552 Comparative Example 2 367

[0200] It can be seen from Table 2 that the gelling time of the powder coating prepared by the present invention is longer than that of the comparative example, and the moderate gelling time is more conducive to the coating obtaining good leveling and curing degree.

[0201] Impact resistance is tested according to GB / T1732-1993:

[0202] Table 3

[0203] Impact / 50cm Example 1 Micro cracks on both sides Example 2 Micro cracks on both sides Example 3 Micro cracks on both sides Example 4 Front and back micro cracks Example 5 Micro cracks on both sides Comparative Example 2 Positive and negative fall off

[0204] It can be seen from Table 3 that the coating formed by the coating of the present invention has higher impact resistance.

[0205] The above description is only a preferred embodiment of the present invention, but the present invention is not limited to the scope of implementation shown. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which still do not exceed the spirit covered by the specification, should be within the protection scope of the present invention.

Claims

1. An environmentally friendly composite high-gloss powder coating, characterized in that: The invention comprises the following ingredients by weight: 90-98 parts of silicon-carbon modified polyester resin, 5-9 parts of curing agent, 5-8 parts of diatomaceous earth, 0.5-0.8 parts of auxiliary agent, 18-23 parts of composite filler, 0.5-0.8 parts of antioxidant, 1-2 parts of tributyl citrate, 1.5-3 parts of calcium stearate, 0.5-1 parts of benzoin and 1-2 parts of leveling agent.

2. The environmentally friendly composite high-gloss powder coating according to claim 1, characterized in that: The auxiliary agent preparation method is: (1) First, methyl methacrylate is added into a reaction kettle, and then an organic solvent is added into the reaction kettle, the temperature is adjusted to 65° C., the mixture is kept warm, and the mixture is stirred and mixed at a speed of 150 r / min for 15 min to obtain a base liquid; (2) adding an initiator to the same organic solvent as in step (1), stirring and mixing at room temperature at a speed of 150 r / min to obtain an initiator solution; (3) The initiator solution prepared in step (2) is added dropwise to the reactor in step (1), and then the mixture is stirred and kept warm at 70° C. for 1.5 hours. A portion of the organic solvent is first removed by atmospheric distillation, and then the remaining organic solvent is removed by reduced pressure distillation. Finally, the mixture is crushed and then sieved through a 350-mesh sieve to obtain an auxiliary agent.

3. The environmentally friendly composite high-gloss powder coating according to claim 2, characterized in that: The organic solvent is xylene; The mixing mass ratio of xylene to methyl methacrylate is 35:5-8; The initiator is dibenzoyl peroxide; The mass fraction of the initiator solution is 3.25%; The mixing mass ratio of the initiator solution to the base liquid is 1:6-8.

4. The environmentally friendly composite high-gloss powder coating according to claim 1, characterized in that: The preparation method of the silicon-carbon modified polyester resin is as follows: Octamethylcyclotetrasiloxane and tetramethyltetravinylcyclotetrasiloxane are added to a reaction kettle in a molar ratio of 3:1-2, and then heated to 50°C, stirred for 30 minutes, and then graphene is added, and the mixture is evacuated to 0.5 Pa, stirred for 2 hours, and then maleic anhydride, a catalyst, and a coupling agent are added, and the temperature is adjusted to 80°C, stirred for 4 hours, and then cooled, discharged, and dried to obtain a modifier; The modifier and polyester resin obtained above are added to a twin-screw extruder for melt extrusion and granulation to obtain a silicon-carbon modified polyester resin.

5. The environmentally friendly composite high-gloss powder coating according to claim 4, characterized in that: The mixing mass ratio of the octamethylcyclotetrasiloxane, graphene, maleic anhydride, catalyst and coupling agent is 10:1-3:2:0.5:

1.

6. The environmentally friendly composite high-gloss powder coating according to claim 5, characterized in that: The catalyst is: potassium persulfate; The coupling agent is a titanate coupling agent.

7. The environmentally friendly composite high-gloss powder coating according to claim 6, characterized in that: The mass ratio of the modifier to the polyester resin is 3-5:40-45.

8. The environmentally friendly composite high-gloss powder coating according to claim 1, characterized in that: The curing agent is curing agent T105; The leveling agent is polyacrylate; The antioxidant is 1010.

9. The environmentally friendly composite high-gloss powder coating according to claim 1, characterized in that: The composite filler is titanium dioxide, calcium titanate, and zeolite powder; The mixing mass ratio of the titanium dioxide, calcium titanate and zeolite powder is 3:15:

1.

10. The method for preparing an environmentally friendly composite high-gloss powder coating according to claim 1, characterized in that: The following steps are involved: S1. First, add silicon-carbon modified polyester resin, curing agent, diatomaceous earth, additives, composite fillers, antioxidants, tributyl citrate, calcium stearate, benzoin, and leveling agent into a mixer, stir and mix for 15 minutes, heat to 120°C under negative pressure, and continue stirring for 20 minutes until the mixture is mixed; The mixing speed is 550r / min; S2. adding the mixture to a twin-screw extruder and subjecting it to melt extrusion; S3. After the melt is extruded through a twin-screw extruder, it is transported to a tablet press for tableting to obtain a sheet, and then the sheet is crushed, sieved, and packaged to obtain an environmentally friendly composite high-gloss powder coating; Among them, the average particle size of the environmentally friendly composite high-gloss powder coating is 40μm.

Citation Information

Patent Citations

  • Graphene oxide / unsaturated polyester composite material and preparation method thereof

    CN102391632A

  • High-temperature resistant and high thermal conductivity nylon composite material and preparation method thereof

    CN108841168A

  • Silicon-containing polyester resin for high-temperature-resistant powder coating

    CN109988491A

  • Powder coating for magnesium alloy

    CN114752285A

  • Polyester resin used for graphene-containing powder coating

    WO2021031377A1